Genetic diversity and vector transmission of phytoplasmas associated with sesame phyllody in Iran - Salehi, M; Esmailzadeh Hosseini, S A; Salehi, E; Bertaccini, A (Folia microbiologica, 2017)
During 2010-14 surveys in the major sesame growing areas of Fars, Yazd and Isfahan provinces (Iran), genetic diversity and vector transmission of phytoplasmas associated with sesame phyllody were studied. Virtual RFLP, phylogenetic, and DNA homology analyses of partial 16S ribosomal sequences of phytoplasma strains associated with symptomatic plants revealed the presence of phytoplasmas referable to three ribosomal subgroups, 16SrII-D, 16SrVI-A, and 16SrIX-C. The same analyses using 16S rDNA sequences from sesame phyllody-associated phytoplasmas retrieved from GenBank database showed the presence of phytoplasmas clustering with strains in the same subgroups in other Iranian provinces including Bushehr and Khorasan Razavi. Circulifer haematoceps and Orosius albicinctus, known vectors of the disease in Iran, were tested for transmission of the strains identified in this study. C. haematoceps transmitted 16SrII-D, 16SrVI-A, and 16SrIX-C phytoplasmas, while O. albicinctus only transmitted 16SrII-D strains. Based on the results of the present study and considering the reported presence of phytoplasmas belonging to the same ribosomal subgroups in other crops, sesame fields probably play an important role in the epidemiology of other diseases associated with these phytoplasmas in Iran.
Keywords: Animals; Sesamum; nemoci rostlin; Írán; Insect Vectors; polymorfismus délky restrikčních fragmentů; DNA bakterií; restrikční enzymy; RNA, Ribosomal, 16S; DNA, Bacterial; Phylogeny; Polymorphism, Restriction Fragment Length; hmyz - vektory; Iran; Hemiptera; DNA Restriction Enzymes; Plant Diseases; Sequence Analysis, DNA; Phytoplasma; ribotypizace; zvířata; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S; Ribotyping